KEBERHASILAN KOPERASI UNIT DESA (KUD) MINA JAYA KOTA BANDAR LAMPUNG BERDASARKAN PENDEKATAN TRIPARTITE - Clara Yolandika; Dyah Aring Hepiana Lestari; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
This research aims to analyze: (1) the financial performance of KUD Mina Jaya reviewed by financial ratio, (2) the contribution of KUD Mina Jaya towards development, and (3) the prosperity rate of KUD Mina Jaya members and compares them based on their status as fisherman.  This research was conducted in KUD Mina Jaya.  There were four level of fisherman, namely ship owner, sailor, ship machine (KKM), and ship crew (ABK).  The numbers of samples are 92 persons that consist of 36 fishermen from the ship with more than 10 ABK and 56 fishermen from the ship with less than 10 ABK.  The data analysis method used was the financial ratio analysis, contribution analysis towards development, the analysis of fishermen’s household income, and the analysis of prosperity rate based on Sajogyo criteria (1997).  The results of this research showed that (1) the financial performance of KUD Mina Jaya reviewed from financial ratio are very good based on solvability and profitability ratio, but it is still in good category based on liquidity ratio, (2) KUD Mina Jaya has contributed towards the development of Lampung Province from 2010 until 2014, with good category based on the obedient of cooperation to pay taxes, the average ratio of labor absorption, and the average of the labor wage rate, and (3) KUD Mina Jaya has been successful enough to make prosperity of its members, unless the ship owner in the ship with more than 10 ABK, which mostly has been categorize in proper life. Key words: development, finance, KUD, prosperity, tripartite